Preliminary Results of Cryoablation for Surgical Treatment of Arrhythmias in Adults With Congenital Heart Disease - Poretti, Giulia; Hoxha, Stiljan; Segreto, Antonio; Jacopo, Gardellini; Sandrini, Camilla; Faggian, Giuseppe; Varrica, Alessandro; Chessa, Massimo; Giamberti, Alessandro; Luciani, Giovanni Battista (Frontiers in Cardiovascular Medicine, 2021)
Background: Arrhythmias in adult congenital heart disease (ACHD) are responsible for the majority of hospital admissions and 20-25% of late deaths. Since need for further cardiac operations is frequent in ACHD, concomitant arrhythmia surgery represents a strategic treatment modality. Material and Methods: A two-center retrospective study was undertaken on cryoablation of supraventricular arrhythmias in 25 conescutive ACHD patients (16/9, M/F, median age 38.5 years, IQR 38-60) operated between 01/2017 and 12/2020. Nineteen (76%) had undergone one or more previous cardiac operations and 8 (32%) one or more trans-catheter ablations. Indications included Fontan conversion in 7 patients, septal defect repair in 6, pulmonary valve replacement in 10 and tricuspid surgery in 2. Open-heart cryoablation included: 4 cavotricuspid isthmus ablations, 19 right-sided Maze for atrial tachycardia/flutter and 2 Cox-Maze III for atrial fibrillation. Results: There were 2 (8%) hospital deaths, unrelated to cryoablation, due to low cardiac output syndrome. There were no intraoperative complications related to cryoablation. Seven (28%) patients required pace-maker implantation due to post-operative atrioventricular block. All patients were discharged on oral antiarrhythmic and anticoagulantion for 6 months. After a median follow-up of 14 months (IQR 7-27) no late mortality was observed. At follow-up, 16/23 (69%) patients are in stable sinus rhythm, 12 without anti-arrhythmic therapy. Two (8.6%) patients had relapse of arrhythmia. Freedom from arrhythmia was 90.9% and cumulative risk of recurrence was 9.6%. Conclusions: Intraoperative cryoablation is safe and effective procedure. Surgical treatment of arrhythmias should always be considered in ACHD, whenever further open-heart repair is needed.